Anxiety managements in patients with myocardial infarction: a literature review - Siwi, Adiratna Sekar; Hidayat, Arif Imam (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2019)
Background: Myocardial Infarction (MI) prevalence is increasing over the world. The patient with MI tend to have anxiety which could worsened their condition and quality of life. The anxiety in patients with MI could increase re hospitalization and mortality rate. Therefore, there is a need of better understanding regarding Anxiety in patients with MI. Objective: This study was conducted to reviews the evidence regarding management of Anxiety in patients with MI. Methods: Literature study was conducted through online searching. PubMed, Else-vier/Science Direct, and Ovid SP, were used and all of the included articles were published in English. Important information and analysis were extracted into tables which consisted of topics and authors, year of publication, design of the study, variables, subjects, intervention, data analysis, result, strength/weakness, and level of evidence. Results: The result of the analysis present the intervention to manage anxiety in patients with MI. There are four main interventions to reduce anxiety in patients with Myocardial Infarction patients, which are aromatherapy, massage, education process, and music therapy. The intervention can be conducted separately or in combine together Conclusion: Aromatherapy, massage, education process, and music therapy effectiveness to reduce anxiety in patients with MI.